Do Institutional and Macroeconomic Factors Matter in IT companies M&As? Evidence from India. Issue 2 (May 2021) - Bhasin, Niti; Soni, Amit; Kar, Rabi Narayan
The liberalisation of the Indian economy, along with targeted policies of the Indian government for the information technology (IT) sector, has led to tremendous growth in this sector. While there has been substantial foreign investment in India in the IT sector through setting up of subsidiaries, joint ventures and acquisitions, Indian firms have also aggressively invested within and outside India through multiple modes. Among different sectors, the IT sector has been the most dominant in terms of mergers and acquisitions (M&As). This article focuses on host country (macroeconomic and institutional) determinants of M&As undertaken by Indian IT firms. Random effect negative binomial model in panel set up was selected to estimate the models. Four models were estimated as per the availability of data for 35–42 countries and for the period 2000–2015. The results for most of the variables in four models were very similar, reflecting robustness of the methodology. Most of the macroeconomic and institutional factors were found to be important determinants of the M&As by Indian IT companies. However, the economic recession of 2008–2009 was found to significantly reduce the M&A activities by Indian IT companies.